FEATURES OF INTRARENAL HEMODYNAMICS IN DIABETES MELLITUS AND CHRONIC KIDNEY DISEASE IN PATIENTS LIVING IN THE SOUTHERN ARAL SEA REGION - Nadzhmutdinova D.K; Sultanov Sh.B. (The Conference Hub, 2025)
One of the severe consequences of diabetes mellitus (DM) is the development of chronic kidney disease (CKD), which should be diagnosed at early stages. Kidney damage develops without pronounced clinical symptoms and in 5-10% of patients with type 2 DM ends with CKD C5. The data of the Khorezm Regional Multidisciplinary Medical Center for the past 5 years on the prevalence of type 2 DM are analyzed. It was found that in Khorezm over the past 5 years, the prevalence of type 2 diabetes mellitus by 2024 in the country reached 5.69 times, and in the capital - 2.16 times. Mortality from CKD C5 in type 2 DM in our country is 1.5%. Identification of markers of early stage diabetic nephropathy seems important, one of the approaches in this regard is the study of the state of intrarenal hemodynamics.
Keywords: type 2 diabetes mellitus, chronic kidney disease, glomerular filtration rate, ultrasound.